L’importance du rôle travail par rapport à d’autres rôles de la vie et sa valeur prédictive dans la transition études-travail - Bujold, Charles; Fournier, Genviève; Drolet, Jean-Louis; Monette, Marcel (Canadian Journal of Counselling and Psychotherapy, 2011)
The present article, while discussing studies that are based upon results obtained during two larger research projects, explores the following questions: (1) What is the importance accorded to the role of work in relationship to other life roles by certain groups that will be entering the job market in the near future? (2) Can the importance given to the role of work be a predictor of success in obtaining employment in a field related to training? and, (3) What role do the variables field of study, gender and age play in the relationship mentioned in the second question? Results which are consonant with theoretical expectations are presented and discussed.